2016
DOI: 10.2141/jpsa.0150150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>in Ovo </i>Injection and Inclusion a Blend of Essential Oils and Organic Acids in High NSPs Diets of Broiler Breeders on Performance of Them and Their Offspring

Abstract: Two factorial completely randomized design trials 2×2 and 2×2×2 were conducted to evaluate the effect of a blend of essential oils and organic acids (Biacid TM ) in broiler breeder diets at two levels, two dietary non-starch polysaccharides (NSPs) levels and in ovo injection of Biacid TM on their progenies performance, respectively. 240 broiler breeders of Ross 308 strain were fed from the age of week 44 th for 12 weeks in four groups. 120 produced eggs from each group were divided in two groups of 60 eggs for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Moreover, there were a significant (P< 0.05) improvement in feed intake and feed conversion ratio in in ovo injection and fed nano thyme oil (T3) followed by (T2) relative to control all over rearing period. The results were in agreement with the finding of Toosi et al (2016) There is a scarcity of information on the in ovo injection of Nano encapsulated essential oil however, dietary inclusion of Nano encapsulated essential oils improved body weight of birds, as revealed by Hosseini and Meimandipour (2018) who studied the effect of thyme oil encapsulated with chitosan on broiler performance which increasing BWG and FCR at different growing periods. This confirmed by Nouri, (2019) who studied the effects of chitosan Nano-encapsulating mint (MEO),thyme (TEO) and cinnamon (CEO) essential oils (EOs) used in the diet on broiler growth performance and revealed that both essential oils and the chitosan Nano encapsulated form had significant (P < 0.05) benefits on improving body weight gain and FCR from 1-42 days.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, there were a significant (P< 0.05) improvement in feed intake and feed conversion ratio in in ovo injection and fed nano thyme oil (T3) followed by (T2) relative to control all over rearing period. The results were in agreement with the finding of Toosi et al (2016) There is a scarcity of information on the in ovo injection of Nano encapsulated essential oil however, dietary inclusion of Nano encapsulated essential oils improved body weight of birds, as revealed by Hosseini and Meimandipour (2018) who studied the effect of thyme oil encapsulated with chitosan on broiler performance which increasing BWG and FCR at different growing periods. This confirmed by Nouri, (2019) who studied the effects of chitosan Nano-encapsulating mint (MEO),thyme (TEO) and cinnamon (CEO) essential oils (EOs) used in the diet on broiler growth performance and revealed that both essential oils and the chitosan Nano encapsulated form had significant (P < 0.05) benefits on improving body weight gain and FCR from 1-42 days.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, there was a significant (P< 0.05) increase in weight of dressing weight, breast muscle and abdominal fat of broiler chicken in treated groups than control ones. The result was in agreement with Toosi et al (2016) who reported that the in Ovo Injection at day 18th of incubation with a Blend of Essential Oils and Organic Acids (Biacid TM ) in High NSPs Diets of Broiler Breeders did not have significant effects on carcass yield. Also the abdominal fat had not affected by in ovo injection of Biacid TM .…”
Section: Carcass Traitssupporting
confidence: 92%
“…In this study, in ovo delivery of EOs reduced hatchability and chick length in broiler chickens. Conversely, most of the very limited studies on in ovo delivered EOs have recorded no effect [ 73 , 74 ] or increased hatchability [ 75 , 76 ]. Compared to this study, the differences in injected EO nature, concentration, volume, injection site, and dosage might potentially explain the observed result.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effects of some plants extracts on broiler chicken growth performance have been reported by Toosi et al [ 35 ], who found that in ovo injection and the inclusion of a blend of essential oils and organic acids (Biacid™) significantly improved the broilers’ hatching eggs.…”
Section: Discussionmentioning
confidence: 94%